ANALISIS TINGKAT PENDIDIKAN DAN POLA ASUH ORANGTUA DALAM PEMBENTUKAN KARAKTER ANAK REMAJA - Kadun, Satria Omega (P3M STT Kristus Alfa Omega, 2022)
The command to educate children is a direct command from God that cannot be ignored. Parents need to realize that the development of children's behavior should be a concern of parents. Parents are responsible as first and foremost educators in the family.Character education is one of the important things in shaping, building and developing children's character. Character education for children starts from the family. The family is the first and foremost institution for laying the foundation of character to children. It is from the family that children first learn about Christian values. The family is the first place where children get teachings and role models about good character. Good character education obtained in the family will bring each child to an understanding of the true self-image. The mistake about self-image will lead child to be inferior, hopeless, feeling useless and unconcerned or other negative feelings. If a child has the correct self-image in a charismatic perspective, the child will understand that his life is extraordinary created in the image and likeness of God, as a person created specifically by God, as a creation that is guarded and guided.Methods The type of research in this paper is library research with a qualitative approach to literature (library research), using descriptive methods which aims to reveal and the relationship between the level of education and parenting patterns in the formation of children's character. The results of this study are that there is an influence between the level of education and parenting patterns in the formation of children's character.